Fragments ou le format comme mise en œuvre et en acte d’une pensée de la Relation - Virginie Brinker (Interfaces)
Fragments is a collective piece combining poetry, visual arts and music. By focusing on the relationships between texts and images – representative of a lifelong cooperation between the poet, slammer and novelist Marc Alexandre Oho Bambe and the visual artist Fred Ebami – this article aims to show that the chosen format achieves the Relation as exemplified by Glissant, by interweaving aesthetic, philosophical and political principles shared by the authors. Fragments also celebrates the performativity of language, turning the work into a new land, a concrete utopia.